2005
DOI: 10.1128/mcb.25.3.1113-1123.2005
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulation of NF-κB Signaling by PIAS1

Abstract: The NF-B family of transcription factors is activated by a wide variety of signals to regulate a spectrum of cellular processes. The proper regulation of NF-B activity is critical, since abnormal NF-B signaling is associated with a number of human illnesses, such as chronic inflammatory diseases and cancer. We report here that PIAS1 ( and bacterial lipopolysaccharide (LPS), activate the NF-B signaling pathway. NF-B is a family of dimeric transcription factors composed of members of the Rel family of DNA bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
162
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 139 publications
(178 citation statements)
references
References 38 publications
11
162
1
Order By: Relevance
“…In addition, PIAS1 repressed the transcriptional activity of a GAL4-p65 fusion protein when assayed using the κB reporter, but not the GAL4 reporter. Consistently, ChIP assays showed that the recruitment of p65 to the endogenous promoter of IκBα, a known NF-κB-target gene, was inhibited in PIAS1-overexpressing cells, but was enhanced in PIAS1-deficient cells [31].…”
Section: Pias In the Regulation Of Nf-κb Signalingmentioning
confidence: 67%
See 4 more Smart Citations
“…In addition, PIAS1 repressed the transcriptional activity of a GAL4-p65 fusion protein when assayed using the κB reporter, but not the GAL4 reporter. Consistently, ChIP assays showed that the recruitment of p65 to the endogenous promoter of IκBα, a known NF-κB-target gene, was inhibited in PIAS1-overexpressing cells, but was enhanced in PIAS1-deficient cells [31].…”
Section: Pias In the Regulation Of Nf-κb Signalingmentioning
confidence: 67%
“…In NF-κB reporter assays, PIAS1 and PIAS3 can repress the transcriptional activity of p65 [31,40]. In addition, the induction of several endogenous NF-κB-target genes, such as those encoding IκBα and Bfl-1, in response to TNF stimulation was inhibited in PIAS1-overexpression cells [31]. Similar to the case of STAT1, purified PIAS1 inhibited the DNA binding activity of NF-κB in mobility gel-shift assays.…”
Section: Pias In the Regulation Of Nf-κb Signalingmentioning
confidence: 83%
See 3 more Smart Citations